임산물 부문 FTA 협상 대응 방안 연구: 한-EU, 한-중 - 이상민 (한국농촌경제연구원, 2007)
This study is mainly designed to suggest the negotiation directions and strategies for the forest products negotiations of the Korea-EU and the Korea-China Free Trade negotiations. The purpose is minimizing negative impacts expected by the results of the agreements. The suggestions are based on the appraisals of the impacts when tariff barriers are removed or reduced, and the impacts are measured through the analysis of the supply and demand as well as the analysis of competitiveness. The contents include recent trade trends of forest products between countries, current industry and market conditions of main products, structural comparison of the tariff systems, appraisals of FTA impacts. For the accurate appraisal of competitiveness on the import market various indices are measured. The import market shares, relative unit price and market comparative advantage index are calculated to find main products to be taken care of seriously. Production values and coefficients of import price in supply functions are estimated to measure the decrease of production value of important items. It is expected that imports of wood products such as plywood(non-coniferous), shaped wood(coniferous), and high density fiberboard would increase if the tariffs are removed. For China the increments would mainly come from most forestry products since its share of Korean import market is about 23% of total import value. To minimize the impacts of FTA with the European Union and China it is required that wood products should be delayed their markets opening as long as possible. In addition to these products other important non-timber products should also be conservative opening. The main wood products such as plywoods, sawnwoods, particle boards and fibers utilize the domestic resource and wood wastes. Consequently they play important roles for the sustainable forest management plan, and protection of their market is very critical. Researchers: Lee, Sang-Min, Myong-Keun Eor, Chul-Soo Chang, and Kyeong-Duk Kim Research Period: 2007.4~2007.12 E-mail address: smlee@krei.re.kr